AUTOMATIC ENERGY SAVING (AES) MODELTO BOOST UBIQUITOUS WIRELESS SENSOR NETWORKS (WSNs) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
We deploy BT node (sensor) that offers passive and active sensing capability to save energy. BT node works in passive mode for outdoor communication and active for indoor communication. The BT node is supported with novel automatic energy saving (AES) mathematical model to decide either modes. It provides robust and faster communication with less energy consumption. To validate this approach, we use two types of simulations: Test bed simulation is performed to automate the server through mobile phone using AES model. Ns2 simulation is done to simulate the behavior of network with supporting mathematical model. The main objective of this research is to access remotely available several types of servers, laptops, desktops and other static and moving objects. This prototype is initially deployed to control MSCS [13] & [14] from remote place through mobile device. The prototype can further be implemented to handle several objects simultaneously in university and other organizations consuming less energy and resources.